Evaluating The Usefulness Of An English Course At Binus University: Freshmen’s Perspectives – Quantitative Approach - Almodad Biduk Asmani (Bina Nusantara University, 2012)
Article examined the feedback and responses provided by Binus University freshmen students concerning their study experiences of taking an English subject, called English Entrant, as part of their compulsory English course program at Binus University during the odd semester of 2010/2011. The research was to find out whether such program has been useful and effective for these students in terms of the teaching quality, course contents and independent learning system commonly applied at Binus University. The research applied the quantitative approach with the focus on finding the general tendency of these students in evaluating the program based on numerical data. In the initial stage of the research, the writer selects the random sample of four to five English Entrant classes ranging from small to large number of students. The results are that the teaching methodology applied in English Entrant tends to be highly acceptable if the lecturers are more communicative and engaging with their students. The speaking format in the classroom is also more preferred by the students if it focuses more on the fluency and clarity rather than the accuracy. Lastly, the independent learning system is more likely to be appreciated by these students if it can provide the proper feedback and improvement for their English learning experiences.